MEDIA COMPETENCE AND MEDIA LITERACY: THE ESSENCE OF CONCEPTS - Olena Murzina (Borys Grinchenko Kyiv Metropolitan University, 2021)
The analysis of the scientific and pedagogical literature, during which the essence of the concepts of «media literacy» and «media competence» is revealed through different views of scientists is performed in the article. We understand media competence as a set of knowledge, skills, abilities that contribute to the search, selection, interpretation, use, evaluation, critical analysis, creation and transmission of media information. The media competence of future doctors we consider as their competence in the application of media technologies in their professional activities. Media competence includes competence of information, competence of communication, informational and communicative competences. Media competence is formed through media literacy, which, in turn, is achieved in the process of media education. It helps individuals to think critically, which helps to form a certain understanding and make competent decisions in response to media information. We define media literacy as a process of personal development through the media and in order to form media culture, develop communicative and creative abilities, critical thinking, skills of finding, interpreting, evaluating and analyzing media information with the help of media technologies. That is, a media literate person is able to control the media and navigate in the media environment, to find the necessary information, can control erroneous messages.